2015
DOI: 10.1115/1.4030901
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Average Reynolds Equation for Rough Bearings With Anisotropic Slip

Abstract: A lubrication theory that includes the coupled effects of surface roughness and anisotropic slips is proposed. The anisotropic-slip phenomena originate from the microscale roughness at the atomic scale (microtexture) and surface properties of the lubricating surfaces. The lubricant flow between rough surfaces (texture) is defined as the flow in nominal film thickness multiplied by the flow factors. A modified average Reynolds equation (modified ARE) as well as the related factors (pressure and shear flow facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Dobrica et al [10] compare stochastic and deterministic models in more detail and conclude that the stochastic model correctly anticipate the trends of the deterministic models for the investigated surfaces. Both studies don't consider slip boundary conditions which is recently reviewed and discussed by Jao et al [11]. Beyond the scope of this study is the 3D consideration of the fluid film using a computational fluid dynamics (CFD) approach [12].…”
Section: Figure 1: Sketch Of a Stribeck Curve With Different Lubricatmentioning
confidence: 99%
“…Dobrica et al [10] compare stochastic and deterministic models in more detail and conclude that the stochastic model correctly anticipate the trends of the deterministic models for the investigated surfaces. Both studies don't consider slip boundary conditions which is recently reviewed and discussed by Jao et al [11]. Beyond the scope of this study is the 3D consideration of the fluid film using a computational fluid dynamics (CFD) approach [12].…”
Section: Figure 1: Sketch Of a Stribeck Curve With Different Lubricatmentioning
confidence: 99%
“…The water-lubricated bearing of the turbine energy recovery integrated machine uses seawater as the lubricating medium, and assuming it is an incompressible fluid, and does not consider the dynamic viscosity μ, density ρ changes with the temperature and pressure during operation. The hydrodynamic pressure of water-lubricated bearing is obtained by solving the average Reynolds equation considering the surface roughness [6,7], which is expressed as…”
Section: Average Reynolds Equationmentioning
confidence: 99%
“…His analyses on bearings with different properties showed that for surfaces where the critical shear stress was set to be approaching zero, very low friction was recorded when compared with conventional bearings. Afterwards Li and co-workers coupled other effects such as the (i) flow rheology [17] and (ii) surface roughness [18] to anisotropic boundary slip to more accurately evaluate the performance of journal bearings. Ma and co-workers [19,20] have proposed an extension of the Tresca slip-model for the analysis of twodimensional journal bearings.…”
Section: Accepted Manuscriptmentioning
confidence: 99%